Local resistance to rising unemployment in the context of the COVID‐19 mitigation policies across Great Britain. Issue 6 (12th December 2020) - Houston, Donald
Abstract: Policies to arrest the rapid spread of the COVID‐19 pandemic resulted in whole sectors of the economy and social life being either entirely locked down or severely curtailed in the Spring of 2020. This paper uses a resilience framework to analyse two aspects of ability to resist rising unemployment at local level across Great Britain during the early part of the COVID‐19 pandemic when full "lockdown" measures were in place: (i) level of pre‐lockdown unemployment; and (ii) share of employment in sectors most affected by the lockdown. Findings reveal that pre‐lockdown unemployment is a stronger predictor than sector mix of the rise in unemployment in the first month of the lockdown. This finding underlines the importance of spatially rebalancing the UK economy, including strong local and regional economic development policies, in order to build resilience to future recessionary shocks. Resumen: Las políticas para detener la rápida propagación de la pandemia de COVID‐19 dieron lugar a que sectores enteros de la economía y la vida social se pusieran en total confinamiento o se restringieran severamente en la primavera de 2020. En este artículo se utiliza un marco de resistencia para analizar dos aspectos de la capacidad para resistir el aumento del desempleo a nivel local en toda Gran Bretaña durante la fase temprana de la pandemia de COVID‐19, cuando se aplicaron medidas de "confinamiento" total: i) el nivel de desempleo anterior al confinamiento; y ii) la proporción de empleo en los sectores más afectados por el confinamiento. Los resultados revelan que el desempleo previo al confinamiento es un predictor más fuerte que la mezcla del aumento del desempleo por sectores en el primer mes del confinamiento. Este hallazgo subraya la importancia de reequilibrar espacialmente la economía del Reino Unido, mediante políticas robustas de desarrollo económico local y regional, a fin de aumentar la capacidad de recuperación ante futuras conmociones debidas a una recesión. 抄録: 2020年春、新型コロナウイルス感染症 (COVID‐19)パンデミックの急速な拡大を阻止するための政策として、結果的に経済と社会生活のすべてのセクターを完全に封鎖するか、または厳しく制限することとなった。本稿では、レジリエンスのフレームワークを用いて、完全な「ロックダウン」措置が実施されたCOVID‐19パンデミックの初期の段階における、英国全国の地方レベルでの失業率の上昇を抑制する能力、すなわち、1)ロックダウン前の失業率のレベル、2)ロックダウンの影響を最も大きく受けたセクターの雇用の割合、という2つの側面を分析する。知見から、ロックダウン前の失業率は、ロックダウンの最初の月の、複数のセクターを合わせた失業率の上昇のよりも強い予測因子であることが明らかになった。これは、将来の景気後退のショックに対するレジリエンスを構築するために、強固な地域経済開発政策を行うなど、英国経済の空間的な均衡を再生することの重要性を強調している。